2020
DOI: 10.1002/asia.202001104
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antiproliferative Activity and Fluorescence of a Dinuclear Gold(I) Bisimidazolylidene Complex via Anthracene‐Modification

Abstract: A straightforward modification route to obtain mono‐ and di‐substituted anthroyl ester bridge functionalized dinuclear Au(I) bis‐N‐heterocyclic carbene complexes is presented. The functionalization can be achieved starting from a hydroxyl‐functionalized ligand precursor followed by transmetallation of the corresponding Ag complex or via esterification of the hydroxyl‐functionalized gold complex. The compounds are characterized by NMR‐spectroscopy, ESI‐MS, elemental analysis and SC‐XRD. The mono‐ester Au comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
6
1
Order By: Relevance
“…It has better selectivity than the reference complexes cisplatin and auranofin. 162 In 2020, Luengo et al reported a series of neutral and cationic heterotrimetallic Re(I)-Au(I) complexes 221a-c. Luminescent studies showed that all the complexes displayed a broad emission band centered between 565 nm and 680 nm. The ancillary ligands were used to modulate the luminescent and/or bioactivity of the metal probes in order to allow the detection of the precise moment of interaction with the biological target.…”
Section: Heterobimetallic Gold(i) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has better selectivity than the reference complexes cisplatin and auranofin. 162 In 2020, Luengo et al reported a series of neutral and cationic heterotrimetallic Re(I)-Au(I) complexes 221a-c. Luminescent studies showed that all the complexes displayed a broad emission band centered between 565 nm and 680 nm. The ancillary ligands were used to modulate the luminescent and/or bioactivity of the metal probes in order to allow the detection of the precise moment of interaction with the biological target.…”
Section: Heterobimetallic Gold(i) Complexesmentioning
confidence: 99%
“…It has better selectivity than the reference complexes cisplatin and auranofin. 162 In 2020, Luengo et al reported a series of neutral and cationic heterotrimetallic Re( i )–Au( i ) complexes 221a – c . Luminescent studies showed that all the complexes displayed a broad emission band centered between 565 nm and 680 nm.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…26 Post-functionalisation strategies typically include biologically native functional groups. 22,23,33 While these have been reported for attaching small molecules, 17,19,22,23,33,34 we only found one example where the post-conjugation to an antibody was facilitated, however here efficacy of the resulting ADCs was hampered due to their low cytotoxicity. 10 The strain promoted azide alkyne cycloaddition (SPAAC) was established by Bertozzi et al as a reliable, selective and versatile technique for the conjugation of biomolecules and was awarded with the Nobel prize in chemistry in 2022.…”
Section: Introductionmentioning
confidence: 86%
“…15,16 To further enhance the selectivity towards cancer cells, several examples of Au( i ) NHC im complexes suitable for post-modification have been reported. They bear inter alia hydroxyl, 17–19 activated ester, 10,20 azide 21 and carboxylic acid 22,23 functional groups, which are available for further bioconjugation. The azide–alkyne cycloaddition (AAC) reaction has proven successful on both pre- and post-functionalisation of Au( i ) NHC im -complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ([Ag(EIA)2]Cl was able to bind the C-terminal dodecapeptide hTrxR(488-499) reproducing the active site of thioredoxin reductase and inhibiting the enzymatic activity. Furthermore, anthracene functionalized silver carbenes were found to inhibit TrxR [35] and their use includes the possibility of imaging upon administration to cells; yet their DNA binding has only been marginally explored [36]. Moreover, it was noted that silver compounds are capable to targeting non-genomic targets such as mitochondria and proteins [30,31,37,38].…”
Section: Introductionmentioning
confidence: 99%